PENGELOLAAN PENDAPATAN ASLI DAERAH (PAD) DARI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KABUPATEN KUANTAN SINGINGI TAHUN 2014-2015 - Gusriadi, Didi; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Importance of taxes for the State to improve local finance. Analyzing the tax management of the earth and rural and urban buildings, the government expects the tax revenue to be more optimal and achieve predetermined targets. This study aims to provide an overview of the management of local revenue from the tax on the earth and rural and urban buildings in kuantan singingi regency in 2014-2015. This research is a descriptive research using qualitative approach as a tool of its analysis. This research was conducted in Kuantan Singingi Regency and took sample data in Revenue Service of Kuantan Singingi Regency. Getting information in this research is primary data and secondary data obtained through documentation and direct interview with informant in this research.Results show that the management of Tax On the Earth and Rural and Urban Buildings in Kuantan Singingi Regency 2014-2015 has not been run efficiently. As the lack of socialization is done to the public so that the taxpayers' interest from the people who are lacking, the lack of staff in managing the taxes of the earth and rural and urban buildings and economic capacity of the people themselves who can not afford to pay local taxes. The government should improve the performance of employees in the management of rural and urban taxes on rural and urban areas in kuantan singingi regency such as holding training in the management so that human resources of employees will become more productive, and prepare funds for socialization to the public so that public awareness in paying Tax increases so that the set targets are achieved.Keywords : Management, Tax On the Earth and Rural and Urban Buildings, Kuantan Singingi